Industrial architecture of the Far East. Blagoveshchensk, Khabarovsk - Bazilevich, Mikhail; Kradin, Nikolai (project baikal, 2021)
The article is focused on industrial architecture of the Russian Far East. Studying the cases of the largest cities in Priamurye, Blagoveshchensk and Khabarovsk, the authors identify the main features of the architecture of factories and other industrial facilities, due to the specifics of the development of the region and its individual cities. The main types of industrial facilities of the second half of XIX – early XX centuries and the principles of their placement in urban areas are considered.
Keywords: industry; factories; works; architecture; Far East